Read-out analog channel with interpolator for signal peak finding. (December 2020) - Shumikhin, V; Atkin, E; Azarov, D; Normanov, D; Ivanov, P; Serazetdinov, A
Abstract: A prototype of an analog channel with a digital processing system for reading signals from GEM detectors is presented. Each channel consists of a charge-sensitive amplifier, a shaper, a switch, an amplifier and a 10-bits ADC. The data from the ADC is processed by the digital system based on an interpolator to find signal peaks. The interpolator uses a 6th order Lagrange polynomial. It maintains peak detection accuracy within 1.1 LSB at 25 MHz ADC sampling rate and 270 ns shaper peaking time.